Synthesis and Crystal Structure of Charge Separate Manganese Complex - Gan, Xiaoping; Chu, Mingjie; Yao, Jianguo; Geng, Wenqian; Zhang, Xiuli; Tian, Yupeng; Zhou, Hongping (Asian Journal of Chemistry, 2013)
A novel complex Mn(taba)2·4H2O [Htaba = 4-(1H-1,2,4-triazol-1-yl) benzoic acid] containing carboxylate-triazole ligands has been synthesized and characterized by elemental analyses, IR and X-ray single crystal diffraction. The crystal of the complex belongs to the triclinic system and P-1 space group with a = 6.153 (5) Å, b = 7.047 (5) Å, c = 12.257 (5) Å, a = 80.366 (5)°, b = 87.997 (5)°, g = 72.673 (5)°, Z = 1, V = 500.1 (6) Å3, Dc = 1.671 g cm-3, μ = 0.723 mm-1, F(000) = 259, Rint = 0.0373, wR = 0.0993. X-ray crystallography shows the manganese(II) ion is coordinated with two triazole nitrogen atoms from two ligands and four oxygen atoms from four water molecules. However, manganese(II) ions only coordinate with N from triazole and not with O from carboxylate group of the ligand, which is different with the reported manganese complexes. In additional, the title complex is a charge separate style that the positive charge center is in manganese atom and the negative charge center is in the carboxylic root of the ligand.